Research and Application of Optimization Technology of Medium Speed Pulverizing System - Gang CHEN; Jinfeng LIU; Dazheng LI; Hua CHENG (发电技术)
It is necessary to optimize the pulverizing system to meet the higher and higher requirements of the power generation unit for the pulverizing system. Through the detailed analysis and research of medium speed pulverizer and pulverized coal pipelines, the crux was found and the optimization measures of pulverizer and dynamic leveling method of pulverized coal pipelines were put forward. The concept of flow field in the mill was introduced into the study of pulverizer optimization, through the improvement of the internal structure of the mill, the overall optimization of the internal flow field of the mill was finally realized, so that the performance of pulverizer was comprehensively and substantially improved. The dynamic leveling of pipeline is to measure the flow deviation of air-powder between pipelines in real time by the pressure difference method under the premise of realizing air-powder homogenization in mill, and according to the measurement results to level the resistance between pipelines in real time by the resistance adjustment device on the pipelines, so as to realize the primary air flow equalizing control between pipelines, and finally realize the air-powder equalizing control of the pulverizing system. The technology can effectively improve the adaptability of the pulverizing system to the coal type and realize the dynamic equalizing control of the air-powder.